From Socrates to Sartre: The philosophic quest - Lavine, T. Z. (Toronto Bantan books, 1984)
This book presents a readable introduction to the lives and times of the great philosophers. It takes us from the inception of Western society Plato's Athens to when the power of Marxism had captured one third of the world. Lavine discusses Western philosophers in terms of the historical and intellectual environment which influenced them, and connects their lasting ideas to the public and private choices we face in America today. The book formed the basis for the PBS television series of the same name.
Keywords: Philosophy history; Philosophy